2012
DOI: 10.4049/jimmunol.1201241
|View full text |Cite
|
Sign up to set email alerts
|

B7x in the Periphery Abrogates Pancreas-Specific Damage Mediated by Self-reactive CD8 T Cells

Abstract: B7x (B7-H4 or B7S1) is the seventh member of the B7 family and the in vivo function remains largely unknown. Despite new genetic data linking the B7x gene with autoimmune diseases, how exactly it contributes to peripheral tolerance and autoimmunity is unclear. Here we showed that B7x protein was not detected on antigen-presenting cells or T cells in both human and mice, which is unique in the B7 family. As B7x protein is expressed in some peripheral cells such as pancreatic β cells, we utilized a CD8 T cell-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 58 publications
(74 reference statements)
3
37
1
Order By: Relevance
“…Similar to previous reports, murine B7-H4 was detected in the islet cells of the pancreas 16,21,22 and the epithelial lining of the lung. 21 Additionally, we uncovered previously unrecognized expression in the esophagus, trachea, salivary gland, mammary, gallbladder, liver, kidney, uterus, and haired skin (Figure 4).…”
Section: B7-h4 Protein Is Expressed In Numerous Murine Tissuessupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to previous reports, murine B7-H4 was detected in the islet cells of the pancreas 16,21,22 and the epithelial lining of the lung. 21 Additionally, we uncovered previously unrecognized expression in the esophagus, trachea, salivary gland, mammary, gallbladder, liver, kidney, uterus, and haired skin (Figure 4).…”
Section: B7-h4 Protein Is Expressed In Numerous Murine Tissuessupporting
confidence: 91%
“…18 Several groups were unable to detect B7-H4 protein in immune cells in vitro, 16,21,22 despite early studies that reported expression. 10,11 Murine B7-H4 protein is detectable in pancreatic islet cells 16,21,22 and in epithelial cells lining the lung, 21 however, expression in other organs has not been reported. Therefore, we developed an immunohistochemistry (IHC) protocol utilizing a novel B7-H4 antibody (AMP6H3).…”
Section: B7-h4 Protein Is Expressed In Numerous Murine Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…It inhibits CD4 and CD8 cell proliferation and cytokine production [53]. It is hardly expressed on professional APC but is expressed on nonlymphoid tissues, mainly epithelial tissues where a role in immune tolerance is postulated [54,[56][57][58]. It is expressed in the lung epithelium and is implicated in attenuating the immune response to bacterial infection in mice [56].…”
Section: B7x (B7-h4/b7-s1)mentioning
confidence: 99%